A DISASTER - A THOUSAND IMPACTS: THE LIFE AND WORK OF GAFUR GHULAM - Makhmudova Sevinch (Western European Studies, 2025)
this article explores the life and work of G'afur G'ulom, a prominent figure in Uzbek literature who left an indelible mark on readers' hearts with his satirical and humorous stories. It delves into the hardships he faced, his journey to "light" after severe trials, and generally recounts events related to his life
Keywords: writer; work; autobiographical; disaster